2018
DOI: 10.1038/s41598-018-33112-8
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Measurements of the Myelin Water Fraction derived from 3D multi-echo GRASE reflect Myelin Content of the Cerebral White Matter

Abstract: Myelin Water Fraction (MWF) measurements derived from quantitative Myelin Water Imaging (MWI) may detect demyelinating changes of the cerebral white matter (WM) microstructure. Here, we investigated age-related alterations of the MWF in normal aging brains of healthy volunteers utilizing two fast and clinically feasible 3D gradient and spin echo (GRASE) MWI sequences with 3 mm and 5 mm isotropic voxel size. In 45 healthy subjects (age range: 18–79 years), distinct regions of interest (ROI) were defined in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 32 publications
2
27
2
Order By: Relevance
“…We observed similar patterns of MWF variability across different ROIs in almost all participants (Fig ). The highly significant paired t ‐tests (Table ) and the consistent patterns of myelin variation between structures (Fig ) illustrate that MWF can assess subtle differences of myelin microstructure at an individual level, expanding upon previous work that reported group averages from smaller cohorts . Although other quantitative metrics (ie, MT ratio derived from MT experiments and fractional anisotropy by diffusion techniques) also detect differences within different WM ROIs, those observed differences may be influenced by nonmyelin‐related factors, such as extracellular water, fiber orientation, and axonal diameter.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We observed similar patterns of MWF variability across different ROIs in almost all participants (Fig ). The highly significant paired t ‐tests (Table ) and the consistent patterns of myelin variation between structures (Fig ) illustrate that MWF can assess subtle differences of myelin microstructure at an individual level, expanding upon previous work that reported group averages from smaller cohorts . Although other quantitative metrics (ie, MT ratio derived from MT experiments and fractional anisotropy by diffusion techniques) also detect differences within different WM ROIs, those observed differences may be influenced by nonmyelin‐related factors, such as extracellular water, fiber orientation, and axonal diameter.…”
Section: Discussionsupporting
confidence: 52%
“…Development of a normative myelin imaging atlas, to which individual patients can be compared, can address these challenges. Atlas‐based approaches for magnetic resonance (MR) methods influenced by myelin have been implemented for a number of different quantitative imaging techniques, including diffusion, T 1 , T 2 , MT, and mcDESPOT‐derived myelin water assessment …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, biomarkers sensitive for these specific developmental patterns of age-related myelin changes are of great interest for researchers studying aging. While many related imaging studies predominantly reported of linear declines of diffusion-based metrics (Bennett et al, 2010;Lebel et al, 2012;Billiet et al, 2015;Rathee et al, 2016), only very few studies found a correlation of MWF estimates with age (Billiet et al, 2015;Arshad et al, 2016;Faizy et al, 2018;Bouhrara et al, 2019). Histopathologically, normal brain-aging is marked by WM degeneration, including myelin pallor (Kemper, 1994), loss of myelinated nerve fibers (Bartzokis, 2004;Bartzokis et al, 2004) and malformation of myelin sheaths (Peters, 2002;Gunning-Dixon et al, 2009).…”
Section: Age-related Decreases Of Regional Mwfs May Reflect Myelin Comentioning
confidence: 99%
“…[9][10][11][12][13] Increasingly, MWF has also been applied in more fundamental fields such as neurobiology and genetics. [14][15][16] In addition to the MWF, the geometric mean T 2 of the IEW peak (IET2) can be reported; both measures have shown clinical relevance. 17 Reproducibility of MWF values has been demonstrated in multi-site and multi-vendor studies, 18,19 but widespread clinical application of MWI has been slowed by long acquisition times.…”
Section: Introductionmentioning
confidence: 99%